2004
DOI: 10.5187/jast.2004.46.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Animunin Powder®on Growth Performance and Blood Components in Nursery and Growing Pigs

Abstract: Two experiments were conducted to investigate the effects of Animunin Powder supplementation on the growth performance and blood components in nursery and growing pigs. In Exp. 1, ninety six pigs(initial mean live weights 27.6 ± 2.63kg) were randomly allocated into four treatments with six replications per each treatment. Four treatments were control(CON), control 0.1% Antibiotics(AB), control 0.1% Animunin Powder (AM), and control 0.1% Antibiotics 0.1% Animunin Powder (ABM). During 4 weeks experiment, ADG of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, digestibility was not reported in either study. In non-ruminants, Shon et al (2004) observed an increase in feed digestibility using a herbal source similar to HAnS. The difference in results could be related to flavour and palatability, which could depend on the type and dose of the phytogenic source (Upadhaya & Kim, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…However, digestibility was not reported in either study. In non-ruminants, Shon et al (2004) observed an increase in feed digestibility using a herbal source similar to HAnS. The difference in results could be related to flavour and palatability, which could depend on the type and dose of the phytogenic source (Upadhaya & Kim, 2017).…”
Section: Discussionmentioning
confidence: 95%